Social-emotional skills associated with teacher training and experience for sentimental teachers: para professores atenciosos - Díaz, Sandra; Cárdenas , Ruth (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This document belongs from the research “Socio-emotional skills associated with training and teaching experience”. The main objective corresponded to the study about link that the Early Childhood Education Degree program at UPTC has made with socio-emotional skills, and the way in which it has been done in his curricular project. With the application of the EINFEM Scale (Cejudo y otros, 2015), the performance, need and presence of socio-emotional skills perceived by a group of students was studied. Aspects such as: linking some of the socio-emotional skills within the curricular project were involved; the areas of the socio-emotional field in which the participants would like to have better training; and the need to integrate determining aspects, related to the emotional subject, in the training process. From the conclusions, it is possible to highlight that, ultimately, the incorporation of strategies to promote the development of socio-emotional skills in teachers in training, improve of learning for life and offers the future teacher valuable skills to face different situations at the personal and professional.